The Impact of Knowledge Management on MNC Subsidiary Performance: The Role of Absorptive Capacity - Mahnke, Volker; Pedersen, Torben; Venzin, Markus (Management international review, 2005)
To date, empirical studies on the impact of knowledge management on the performance of MNC subsidiaries remain few in number. This study examines the effect of knowledge management tools upon absorptive capacity, knowledge-flows and performance with unique data from subsidiary units in a large German MNC -HeidelbergCement. Treating absorptive capacity as an endogenous construct subject to managerial discretion, we show how knowledge management tools unfold their performance impact through their significant influence on absorptive capacity and knowledge inflows.